Design of Ti-Nb-Cr alloys for hydrogen storage: exploring hydride destabilization through Nb/Ti ratio adjustment - Dias, Gabriela Chimello Mayer (2024)
Hydrogen is emerging as a promising alternative to fossil fuels amidst concerns over depleting reserves and environmental impacts. However, efficient hydrogen storage remains a significant challenge for widespread application. Solid-state storage, especially using metal hydrides, presents a promising solution for efficient storage at moderate pressure conditions. Alloys with a body-centered cubic (BCC) structure, such as those in the Ti-V-Cr and Ti-V-Nb-Cr systems, have shown promising properties. Notably, studies specifically on hydrogen storage in Ti-Nb-Cr ternary system alloys are scarce, with results emphasizing high hydride stability. To enhance the efficiency of MH-based hydrogen storage systems, achieving hydrogen desorption at low temperatures is crucial. In this context, this study investigates the hydride destabilization in the Ti-Nb-Cr system by designing alloys with a reduced concentration of the stronger hydride-forming element, Ti, and an increased fraction of the weaker hydride-forming element, Nb. To favor a predominant body-centered cubic (BCC) phase, Cr content was maintained below 35 at.%. The impact of these compositional adjustments on key properties for solid-state hydrogen storage was thoroughly examined. Trends in the plateau pressures of the Pressure-Composition-Temperature (PCT) diagrams were predicted using a thermodynamic model. Four compositions were studied: Ti1.0Nb1.0Cr1.0, Ti0.8Nb1.4Cr1.0, Ti0.6Nb1.8Cr1.0, and Ti0.4Nb2.2Cr1.0. These alloys were synthesized via arc melting and predominantly exhibited a BCC phase with a fraction of C15 Laves phase. All alloys showed rapid absorption kinetics and attained maximum hydrogen storage capacities of 2.79 wt.%, 2.30 wt.%, 2.23 wt.%, and 2.09 wt.%, as the Nb/Ti ratio increased. After 10 cycles, capacities decreased by 0.20 wt.%, 0.16 wt.%, 0.17 wt.%, and 0.26 wt.%, respectively. PCT diagrams indicated that increasing the Nb/Ti ratio resulted in higher plateau pressures, nearly reaching 1 bar in absorption for the Ti0.4Nb2.2Cr1.0 alloy. Thermal analysis revealed that the enthalpy of desorption became lower with increasing the Nb/Ti ratio, indicating hydride destabilization.